Legislative organization and executive success rate at the subnational level: a comparison of Brazil and Germany, 1990-2010 - Weber, Bernd; Praça, Sérgio (Revista Ibero-Americana de Estudos Legislativos, 2014)
How does parliamentary organization affect the legislative success rate of the executive in presidential and parliamentary systems at the subnational level? Why are some governors much more successful than others even though they serve under the same basic constitutional designs? This essay explores these questions with a comparison of Brazilian and German states from 1990 to 2010. Our main findings are that governors’ success rates in both Brazil and Germany seem not to be associated with centralization of legislative institutions. This means that coalition management and party politics may play a larger role than expected by the literature. Other factors, such as “minor” and neglected legislative arrangements can compound the governors’ strength and allow them to reach Westminster levels of legislative success.